Pengaruh Pengetahuan Dewan Tentang Anggaran Terhadap Pengawasan Keuangan Daerah Dengan Akuntabilitas Publik Sebagai Variabel Pemoderasi - Trini Wulandari; Deviani Deviani (Wahana Riset Akuntansi, 2013)
This research examines the influence of regional representative board knowledge to the regional finance control with public accountability as moderating variabel. Population in this research is Regional Representatives Board of Regency and City in West Sumatera province. Samples selection by purposive sampling participated by 297 respondents. The data collecting technique used in this research in by giving questionnaires to the Budget Section of the Regional Representatives Board of Regency and City in West Sumatera province. The analysis methode used in this research is moderated regression analysis. The result of this research concludes that the regional representatives board knowledged toward budget gives positives and significant effect to the regional financial control. While public accountability has no positive and significant effect to the relation between the board knowledged on budget and the regional financial control. Keywords: regional representative board, public accountability, regional finance, board knowledge